Can the type of preheated resin composite influence the microtensile bond strength of ceramic restoration to human dentin? - Rodrigues, Vinícius Anéas [UNESP]; Luz, Julio Nogueira [UNESP]; Dantas da Silva, Bianca Cristina; da Silva, Nathalia Ramos; Bottino, Marco Antonio [UNESP]; de Melo Marinho, Renata Marques [UNESP]; Özcan, Mutlu; de Assunção e Souza, Rodrigo Othávio (My University, 2021)
The aim of this study was to evaluate the effect of the type of preheated resin composite on the microtensile bond strength (µTBS) between dentin and feldspathic ceramic inlays. Thirty healthy human premolars received inlay preparations for feldspathic ceramic restorations and were then divided into three treatment groups according to the luting agent (n = 10): Conventional Resin Cement (RC), Preheated Nanofilled Methacrylate-Based Resin composite (MB), and Preheated Microhybrid Silorane-Based Resin composite (SB). The composite resin was preheated to 55 °C, considering the cementation group. After cementation, the sets were cut into slabs with a bonding area of 1 mm2 to be further submitted to the µTBS test (0.5 mm/min, and10 Kgf load cell). One-way ANOVA and Tukey test (p <.5) were performed to analyze the bond strength data (MPa). Failures were observed under a stereomicroscope and representative specimens were evaluated using a Scanning Electron Microscopy (SEM). ANOVA revealed that the type of luting agent utilized was significant (p =.001). Bond strength values for the RC (7.37 ± 1.27 MPa)A and MB (6.98 ± 1.96 MPa)A treatment groups were similar and greater than the SB (4.74 ± 1.65 MPa)B. Adhesive failures between the cementing agent and ceramic were prevalent for the treatment groups. The preheated nanofilled methacrylate resin-based composite technique can promote bond strength similar to resin cement, whereas preheated silorane-based resin composite as a luting agent should be seen with caution. Thus, we concluded that the type of luting agent has influenced the µTBS of feldspathic restoration to dentin.
Keywords: cementation; indirect restoration; Microtensile bond strength; preheating; resin composite